Mental Illness in Patients with Heart Failure Admitted in Cardiac Ward in a Tertiary Care Hospital in Nepal - Poudel, Lata Gautam; Chettri, Trishna Ghosh; Poudel, Samir Kumar (Journal of National Heart and Lung Society Nepal, 2024)
Background: Heart failure (HF) is associated with significant psychiatric comorbidity, particularly anxiety and depression, which have adverse impact on patient outcomes. Despite the established relationship between mental illness and cardiovascular disease globally, this area of research in Nepal remains understudied. The objective of this study is to determine the prevalence of mental disorders, specifically anxiety and depressive disorders, in patients with heart failure admitted to a tertiary care hospital in Nepal, and to examine the association between mental disorders and treatment outcomes. Methods: This prospective observational study was conducted at National Academy of Medical Sciences, Bir Hospital, Kathmandu, Nepal. A total of 113 consecutive adult patients admitted with a primary diagnosis of HF, made by consultant cardiologists, were enrolled between January 2024 and April 2025. Critically ill or non-consenting patients were excluded. Psychiatrist diagnosed anxiety and depressive disorders using clinical interview per ICD-10 criteria. Demographic data and hospital outcomes were recorded. Statistical analysis was performed using SPSS version 23, with p-value<0.05 considered statistically significant. Results: The mean age of participants was 58.13±14.23 years (range 26-86 years), with 57.5% females and 42.5% males. The study population comprised 17.8% young adults, 47.8% middle-aged, 27.4% elderly, and 7.1% very elderly individuals. The overall prevalence of mental illness was substantial in heart failure patients-anxiety in 52.21% and depression in 31.85%. Gender and mental illnesses did not show statistically significant association (p-value=0.110). Conclusion: Mental disorders are prevalent among heart failure patients in Nepal, consistent with global trends. These findings underscore the need for integrated psychiatric screening and management in cardiac care settings to optimize patient outcomes.